Civilizing Torture: An American Tradition, by W. Fitzhugh Brundage - John Wilson Schiemann (Torture)
Civilizing Torture amplifies the echoes of pre-9/11 American experiences with torture – dehumanization of the enemy, justifications for torture, claims of efficacy, the fleeting nature of the public debate about torture and what it meant, and more – and in so doing reminds us of how the traditional seems forever new — and so is repeated all too often.